Emergency gates - model scale tests at turbine runaway condition. Issue 1 (June 2021) - Angulo, M.; Rivetti, A.; Díaz, L.; Lucino, C.; Liscia, S.
Abstract: Emergency gates are the last link in the chain of safety of turbo-groups in case of distributor failure, safeguarding the power station from severe damage. These gates can be located at the turbine intake or at the outlet of the draft tube and can be controlled by gantry cranes or hoist hydraulic cylinders. Gates must descend with high flow for a short time to prevent the turbine from spinning at runaway velocity for periods longer than admissible, as that would entail the rise of uplift and downpull forces that may jeopardize their stability. Indeed, at the prototype scale, the closing maneuver entails a certain risk, because of which it is usually tested avoiding extreme conditions. In this work, the operation of emergency gates was tested against more severe conditions on a reduced-scale physical model. The case study involves three emergency gates controlled by gantry cranes and located at the intake of a large Kaplan turbine which underwent high levels of vibration when operated at prototype scale. Model tests were aimed at detecting and quantifying hydraulic phenomena that might emerge during operation with an eye on the proposal of alternative designs. Unlike most tests of this sort, the experimental setup includes the runner of the turbine assembled on a test rig, which allows for a more realistic flow distribution along the vanes during the gate closure under runaway conditions. Steady state tests were carried out under runaway conditions, while stems of servomotors enabled the regulation of the position of the gate. Downpull forces were found to start at 12 % of the gate opening. Flow asymmetry was observed, gate on the left of the semi-spiral casing being the most affected by higher flow velocities. The runner vortex rope frequency was measured also at gate lip for some particular conditions.